A Paradigm of Calendaring‐Driven Electrode Microstructure for Balanced Battery Energy Density and Power Density. Issue 2 (23rd November 2022) - Zhan, Renming; Ren, Dongsheng; Liu, Shiyu; Chen, Zhengxu; Liu, Xuerui; Wang, Wenyu; Fu, Lin; Wang, Xiancheng; Tu, Shuibin; Ou, Yangtao; Ge, Hanlong; Wong, Andrew Jun Yao; et al.
Abstract: The microstructure of an electrode plays a critical role in the electrochemical performance of lithium‐ion batteries, including the energy and power density. Using a micrometer‐scale Wadsley–Roth phase TiNb2 O7 active material with Li intercalation chemistry as a model system, the relationship between electrochemical performance and microstructure of calendared electrodes with same mass loading but different electrode parameters is studied by both experimental investigation and theoretical modeling, providing a paradigm of calendaring‐driven electrode microstructure for balanced battery energy density and power density. Along with the reduction in porosity, ion and electron diffusion distance decreases, which is beneficial for charge transfer and rate capability. Nevertheless, the narrowed ion diffusion pathway increases the resistance for ion diffusion. The rate capability, volumetric capacity, and materials utilization are thus predominantly restricted by the microstructures of the electrode, providing fundamental insights into electrode microstructure design for different applications. As an example, an optimized TiNb2 O7 electrode with compaction density of ≈2.5 g cm ‐3 and mass loading of ≈8.5 mg cm ‐2 provides the highest specific charge capacity of 271.3 mAh g ‐1 at 0.2 C in half cell configuration and 70.4% capacity retention at 6 C in full configuration, enabling balanced energy density and power density of batteries. Abstract : In this article, the dependence of electrochemical performance on dual variation of electrode compaction density and porosity is studied via experiments and theoretical modeling. A paradigm of calendaring‐driven electrode microstructure is realized for balanced battery energy density and power density using a Wadsley–Roth phase TiNb2 O7 anode as an example.